2023
DOI: 10.1002/anie.202218146
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergent Synthesis of Allenes with α,β‐Adjacent Central Chiralities Empowered by Synergistic Pd/Cu Catalysis

Abstract: The stereodivergent synthesis of allene compounds bearing α,β-adjacent central chiralities has been realized via the Pd/Cu-catalyzed dynamic kinetic asymmetric alkylation of racemic allenylic esters. The matched reactivity of bimetallic catalytic system enables the challenging reaction of racemic aryl-substituted allenylic acetates with sterically crowded aldimine esters smoothly under mild reaction conditions. Various chiral non-natural amino acids bearing a terminal allenyl group are easily synthesized in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 124 publications
0
14
0
Order By: Relevance
“…Recently, Zhang and Ma have successfully developed a stereodivergent Pd/Cu catalytic system for the enantioselective and diastereoselective allenylation of aldimine esters with racemic 2,3-allenylic acetates (Scheme 23). 37 Both aryl-and alkyl-substituted allenylic substrates were compatible with the reaction conditions, affording a wide range of chiral non-natural amino acids bearing a terminal allenyl group with vicinal central chiralities in high yields and with excellent diastereoselectivity and enantioslectivity (up to 420 : 1 dr and 499% ee). Control experiments, kinetic studies, and theoretical calculations suggested that the easy interconversion between the Z 3 -butadienyl palladium intermediate possessing a weak CQC/Pd coordination bond and a stable Csp 2 -Pd bond is beneficial for the DyKAT process of racemic allenylic substrates.…”
Section: Asymmetric Propargylation and Allenylation Of Aldimine Estersmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Zhang and Ma have successfully developed a stereodivergent Pd/Cu catalytic system for the enantioselective and diastereoselective allenylation of aldimine esters with racemic 2,3-allenylic acetates (Scheme 23). 37 Both aryl-and alkyl-substituted allenylic substrates were compatible with the reaction conditions, affording a wide range of chiral non-natural amino acids bearing a terminal allenyl group with vicinal central chiralities in high yields and with excellent diastereoselectivity and enantioslectivity (up to 420 : 1 dr and 499% ee). Control experiments, kinetic studies, and theoretical calculations suggested that the easy interconversion between the Z 3 -butadienyl palladium intermediate possessing a weak CQC/Pd coordination bond and a stable Csp 2 -Pd bond is beneficial for the DyKAT process of racemic allenylic substrates.…”
Section: Asymmetric Propargylation and Allenylation Of Aldimine Estersmentioning
confidence: 94%
“…35 Scheme 23 Synergistic Pd/Cu catalysed dynamic kinetic alkylation of racemic allenylic acetates with aldimine esters reported by Ma and Zhang in 2023. 37 Scheme 24 Cu-catalysed radical C-N cross-couplings reported by Fu and Peters in 2012 and 2013. 39,40 between the laboratories of Fu and Peters continued as the group extended this method to alkyl iodides, relying again on radical generation by a carbazole-ligated copper complex (Scheme 24, bottom).…”
Section: Copper-catalysed Asymmetric C-n Cross-couplingmentioning
confidence: 99%
“…86 87 88 89 90 91 92 Through these efforts, propargylic alkylation, the hydrofunctionalization of 1,3 dienes, allenes and enynes, and the challenging construction of non-adjacent 1,3-stereocenters has been achieved (Scheme 11 C). 93 94 95 96 97 98 99 100 101…”
Section: Multi-catalysismentioning
confidence: 99%
“…However, in the reported examples, only terminal allyl alcohol derivatives were employed as allylation reagents (Figure a). Combined catalytic systems other than chiral aldehyde/palladium catalysis could promote the reactions of amino acid derivatives with both terminal and internal allylic alcohol derivatives, but the usage of N- protected amino acid derivatives was necessary (Figure b) . The catalytic asymmetric α-allylation of N- unprotected amino acid derivatives with internal allylic alcohols will provide a more straightforward way, leading to α,α-disubstituted α-amino acid derivatives bearing two vicinal chiral centers.…”
mentioning
confidence: 99%